Town, Richard: my experience as a Canadian Defence Attaché (March 14, and 24, 2017) - Town, Richard; Currie, Heather (2017)
ABSTRACT: This audio recording provides an overview of Captain Town’s career in the Royal Canadian Navy. The interview covers the breadth of his career, from his first experience as a Sub-lieutenant on the Athabaskan, to commanding the HMCS Annapolis where he led one of the first mixed gender crews. Career highlights also include acting as the On-Scene Commander for the search and recovery operation of the crash of SWISSAIR Flight 111. It also includes his experience as the Chief of Staff, NATO Standing Naval Force during the arms embargo against the Federal Republic of Yugoslavia.